CORPUS TECHNOLOGIES IN TEACHING ACADEMIC WRITING - Radjabova, Gulnoza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
There have been a lot of investigations in the sphere of Corpus Linguistics and Corpus-based Language pedagogy which have revealed the insights and methodologies of corpus linguistics to second language writing pedagogy and research. However, there are still gaps referring to the empirical application of corpus tools in teaching writing. The following article is aimed to examine the effects of corpus tools application in writing classes, in particular the how corpus technologies can be incorporated into writing instruction. The research has involved qualitative and quantitative methods of investigation, as well as some surveys and interviews. The results of the research have shown that corpora can be used as a meaningful and authentic reference for language materials which provide learners with real usage of words and collocation patterns. More importantly, the integration of corpus into the writing classroom appears to provide the solution to the writing problems of learners and also promote their independent learning skills. Besides, the study focuses on the necessity to increase the learners’ willingness and success in using corpora. The findings also suggest that teachers, before incorporating corpus-based teaching into their instruction, need to understand the basic principles of the usage of corpus technologies and how these technologies can be effectively integrated into the writing instruction.
Keywords: corpus; corpus technologies; corpus linguistics; corpusbased language pedagogy; writing instruction